"Your Heart can Dance to them Even if your Feet Can't": Anton Boisen, Older People, and the Therapeutic Value of Hymns. Issue 3 (8th October 2014) - Eldred, Janet B.; Lowis, Michael J.; Jewell, Albert J.; Jackson, Michael I.
Abstract : Anton Boisen's mid-twentieth-century Hymns of Hope and Courage provided the inspiration for a survey of early-twenty-first-century people. The authors used Boisen's "psychotherapeutic considerations" underpinning his hymnal, which had been compiled for use in hospitals for the mentally ill, as the benchmark to compare the responses from the general population to questions about whether and how hymns can raise their spirits. A brief questionnaire, distributed in the UK, elicited responses from 394 women and men, the majority (73 per cent) aged 65–99. Of the 394 respondents, 95 per cent confirmed that certain hymns "sometimes" or "often" make them feel better, with 64 per cent saying that this was the result of the words and tunes together, and that most of the time they needed to sing the hymns rather than simply listen to them. Where reasons could be identified by the respondents, key factors such as the evocation of memories, the reinforcement of beliefs, help when facing problems, knowing one was not alone, and praise of and thanks to God all tie in closely with Boisen's ideas. The authors use these results to make practical suggestions for worship leaders and hymn writers, particularly among those who work with older people. Areas for further investigation are also provided.